1999
DOI: 10.1042/bj3430467
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intracellular localization of calpastatin during calpain activation

Abstract: Localization of the two main components of the Ca2+-dependent proteolytic system has been investigated in human neuroblastoma LAN-5 cells. Using a monoclonal antibody which recognizes the N-terminal calpastatin domain, it has been shown that this inhibitory protein is almost completely confined in two granule-like structures not surrounded by membranes. Similar calpastatin distribution has been found in other human and in murine cell types, indicating that aggregation of calpastatin is a general property and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 15 publications
4
60
1
Order By: Relevance
“…sufficient to activate calpains. Furthermore, structural and biochemical data indicate that calpastatin might bind preferentially to calcium-activated calpains (Barnoy et al, 1999;Tullio et al, 1999), suggesting that this is an attenuation mechanism rather than a preventive one.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…sufficient to activate calpains. Furthermore, structural and biochemical data indicate that calpastatin might bind preferentially to calcium-activated calpains (Barnoy et al, 1999;Tullio et al, 1999), suggesting that this is an attenuation mechanism rather than a preventive one.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…Calpain and calpastatin are predominantly cytosolic proteins, indicating that calpain must somehow escape the inhibitory control of calpastatin to become fully activated. It has been suggested that subcellular compartmentalization of either calpain or calpastatin may regulate calpain activity within cells (35,60). Modulation of the balance between protein levels of calpain relative to calpastatin could also represent a mechanism for regulating calpain activity.…”
mentioning
confidence: 99%
“…At a molecular level calpastatin protein undergoes structural modifications determining its specificity and inhibitory efficiency (13,45) as well as its intracellular localization. This is particularly evident in neuroblastoma cells (46), in which calpastatin is normally present in a phosphorylated and aggregated form localized in a specific position close to the nucleus. After hydrolysis of these phosphate groups by a protein phosphatase, the dephosphorylated inhibitor diffuses into the cytosol and acquires a significant increase in its inhibitory efficiency (45).…”
Section: Discussionmentioning
confidence: 99%